2015
DOI: 10.1105/tpc.15.00466
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis Plasma Membrane Proton ATPase Modulates JA Signaling and Is Exploited by the Pseudomonas syringae Effector Protein AvrB for Stomatal Invasion

Abstract: ORCID IDs: 0000-0003-0202-3890 (C.L.); 0000-0002-9943-2975 (J.-M.Z.) Stomata are natural openings through which many pathogenic bacteria enter plants. Successful bacterial pathogens have evolved various virulence factors to promote stomatal opening. Here, we show that the Pseudomonas syringae type III effector protein AvrB induces stomatal opening and enhances bacterial virulence in a manner dependent on RPM1-INTERACTING4 (RIN4), which promotes stomatal opening by positively regulating the Arabidopsis plasma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 36 publications
4
88
2
Order By: Relevance
“…Thus, guard cells can be directly targeted by pathogen effectors to promote colonization. Consistent with this finding, AvrB has been demonstrated to promote bacterial growth and stomatal opening upon surface inoculation (Zhou et al, 2015). Collectively, these data indicate that effectors can be directly delivered into cells of the leaf surface in order to enhance entry into the leaf interior and suppress defense responses.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, guard cells can be directly targeted by pathogen effectors to promote colonization. Consistent with this finding, AvrB has been demonstrated to promote bacterial growth and stomatal opening upon surface inoculation (Zhou et al, 2015). Collectively, these data indicate that effectors can be directly delivered into cells of the leaf surface in order to enhance entry into the leaf interior and suppress defense responses.…”
Section: Discussionsupporting
confidence: 61%
“…Mean and SD values were calculated from scores of >7 plants. Zhou et al, 2015). Here, we demonstrated that AvrB and AvrPtoB can be directly delivered into guard cells, which flank stomatal pores, upon surface inoculation using the GFP strand system.…”
Section: Discussionmentioning
confidence: 79%
“…A similar observation was reported by Zhou et al (2015), in which protein degradation of JAZs was promoted by RIN4 or AHA1 in transient coexpression assays in tobacco without addition of COR or JA-Ile. It is conceivable that this event is mediated by endogenous JA, given that there is a certain level of JAs, e.g.…”
Section: Discussionsupporting
confidence: 87%
“…This may potentially generate an unknown signal that promotes the interaction between COI1 and JAZ proteins to degrade JAZ and enhance JA signaling. In addition, AvrB induces MYC-mediated expression of ANAC019, ANAC055, and ANAC072 genes in Arabidopsis and the tomato NAC homolog JASMONIC ACID2-LIKE gene to repress SA responses (Du et al, 2014;Zhou et al, 2015;Gimenez-Ibanez et al, 2017). Therewith, like COR, AvrB appears to regulate stomatal opening through manipulating the SA-JA antagonism.…”
Section: Type III Secreted Effectorsmentioning
confidence: 99%
“…For example, COR requires RPM1-INTERACTING4 (RIN4), a negative regulator of plant innate immunity, to open the stomatal pore as evidenced by the facts that neither Pst DC3000 nor COR was able to reopen stomata of rpm1/ rps2/rin4 mutants (Liu et al, 2009;Zhou et al, 2015;Lee et al, 2015). The perception of flg22 via the FLS2 receptor leads to phosphorylation of the plasma membrane H + -ATPases and subsequent alkalization of the apoplast, which, along with the induction of ROS via NADPH oxidase RbohD, triggers stomatal closure (Liu et al, 2009;Li et al, 2014).…”
Section: Phytotoxinsmentioning
confidence: 99%